Answer:
![f(x) = -(1)/(3)x - 4](https://img.qammunity.org/2023/formulas/mathematics/college/emrf8k1hjgmdi053bd4lvyuv36h7oien0l.png)
Explanation:
First, find the slope of the line (m) using the equation
![m=(y_2 - y_1)/(x_2 - x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/1rw2463r5uihaztygqq8wertlli3mqnn11.png)
FOR (-6, -2) and (-9, -1):
,
![y_1 = -2](https://img.qammunity.org/2023/formulas/mathematics/college/kpql37hlmw9bbutprdnjr9rtqi8c86wna8.png)
,
![y_2 = -1](https://img.qammunity.org/2023/formulas/mathematics/college/8xtpl40b4o9vy5ypauy2l6zmwrycvip7de.png)
When plugging these values into the slope equation, we get:
![m = (-1 - (-2))/(-9-(-6)) = (1)/(-3) = -(1)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/t8z8w0vlfdr4w518i11fcrb1difm904jt9.png)
So, the slope of the line is -1/3.
Next, plug the slope value along with one of the given points on the line into the point-slope equation with point (a, b):
![y - a = m(x - b)](https://img.qammunity.org/2023/formulas/mathematics/college/6m3r2lsrr4uaanfgtjany3w9515lizlphx.png)
![y - (-2) = -(1)/(3)(x - (-6))](https://img.qammunity.org/2023/formulas/mathematics/college/dfcb3ruhqub9a7bv16fpsrjhmpeo1smr4s.png)
and simplify.
![y + 2 = -(1)/(3)(x + 6)](https://img.qammunity.org/2023/formulas/mathematics/college/o7korzsm18q18qjvgfuw69cdaowksnc759.png)
![y + 2 = -(1)/(3)x - 2](https://img.qammunity.org/2023/formulas/mathematics/college/2b7ugvu1cxkeicvfd3b17r7b6ah3zquau7.png)
![y = -(1)/(3)x - 2 - 2](https://img.qammunity.org/2023/formulas/mathematics/college/oqh610qyu4hxpl70bx8bu4n0lhmh5us9pr.png)
![y = -(1)/(3)x - 4](https://img.qammunity.org/2023/formulas/mathematics/college/vcavl6wzop4hmz0mtunoavhan9g383liwn.png)
Finally, replace y with f(x) to get:
![f(x) = -(1)/(3)x - 4](https://img.qammunity.org/2023/formulas/mathematics/college/emrf8k1hjgmdi053bd4lvyuv36h7oien0l.png)